Prof. Maja Razbojnikova-Frateva as a translator and mediator in the dialogue between cultures - Kileva-Stamenova, Reneta (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2023)
The paper presents the contribution of Prof. Maja-Razbojnikova Frateva as a translator.